Advances in chemical engineering. Volume 43, Control and optimisation of process systems - Pushpavanam, S.; ScienceDirect eBooks (Amsterdam ; Burlington, MA : Elsevier/Academic Press, 2013)
Advances in Chemical Engineering was established in 1960 and is the definitive serial in the area. It is one of great importance to organic chemists, polymer chemists, and many biological scientists. Written by established authorities in the field, the comprehensive reviews combine descriptive chemistry and mechanistic insight and yield an understanding of how the chemistry drives the properties. This volume focuses on control and optimisation of process systems. Advances in Chemical Engineering was established in 1960 and is the definitive serial in the area. It is one of great importance to organic chemists, polymer chemists, and many biological scientists. Written by established authorities in the field, the comprehensive reviews combine descriptive chemistry and mechanistic insight and yield an understanding of how the chemistry drives the properties. This volume focuses on control and optimization of process systems.
Includes bibliographical references and index.
Elsevier
Keywords: Chemical engineering; Systems engineering; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Chemical engineering; Systems engineering; Electronic books